PENERAPAN STRATEGI MENTOR-MENTORING BERMEDIA LINKTREE UNTUK MENINGKATKAN ADOPTION RATE RAPOR PENDIDIKAN SEKOLAH BINAAN - Purwanto, Wahyu (Jurnal Lingkar Mutu Pendidikan, 2024)
The use of educational report cards as a tool for evaluating educational performance is often not optimal in a number of educational units. This indicates the low level of adoption of education report cards as an effective evaluation instrument. This article explores the application of mentoring with the Mentoring-Monitoring strategy as an effort to increase the adoption of educational report cards. The research method used involved a qualitative descriptive approach at 10 target schools. The research results show that the implementation of mentoring with the Mentoring-Monitoring strategy is very effective in increasing the adoption of educational report cards in assisted education units. After the mentoring activity, the results of the adoption of educational report cards increased from 0 schools to 10 schools or a 100% increase in the adoption rate of educational report cards. This also had an impact on increasing the district's adoption rate, namely an increase of 48.89% for the educational report card exploration indicator. The Monitoring activity steps in the Mentor-Monitor strategy function to ensure the successful adoption rate of education report cards by using them quality as a form of effort to improve schools through data-based planning.